2006
DOI: 10.3354/meps309233
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting patterns of growth and migration of tropical anguillid leptocephali in the western Pacific and Indonesian Seas

Abstract: In order to improve understanding of the larval migration and early life history characteristics of 4 tropical eels, Anguilla marmorata, A. bicolor pacifica, A. celebesensis and A. borneensis, the leptocephali, metamorphosing leptocephali and oceanic glass eels collected during 8 cruises in the western Pacific and Indonesian Seas from 1991 to 2002 were analyzed. The leptocephali of A. celebesensis and A. borneensis were collected only in close proximity to their relatively small species ranges in the Indonesia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
83
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(87 citation statements)
references
References 38 publications
4
83
0
Order By: Relevance
“…The sampling surveys conducted in the northern Indonesian Seas region have indicated that anguillid leptocephali are usually present but not at high abundances. This was the case in the Danish survey (Jespersen 1942) and during recent surveys (Aoyama et al 2003;Kuroki et al 2006;Wouthuyzen et al 2009) (Fig. 6).…”
Section: Distribution and Dispersal Of Anguillid Larvaesupporting
confidence: 53%
See 1 more Smart Citation
“…The sampling surveys conducted in the northern Indonesian Seas region have indicated that anguillid leptocephali are usually present but not at high abundances. This was the case in the Danish survey (Jespersen 1942) and during recent surveys (Aoyama et al 2003;Kuroki et al 2006;Wouthuyzen et al 2009) (Fig. 6).…”
Section: Distribution and Dispersal Of Anguillid Larvaesupporting
confidence: 53%
“…Japanese scientists then discovered the spawning area of A. japonica in 1991 (Tsukamoto 1992) after smaller and smaller larvae were collected farther offshore . These surveys expanded out across the Indo-Pacific (Aoyama et al 2003(Aoyama et al , 2007Kuroki et al 2006) with evidence of offshore spawning by eels in the western South Pacific being found (Kuroki et al 2008;Aoyama 2009) and local spawning by eels in the Indonesian seas being discovered (Aoyama et al 2003). These collections and genetic or morphological information about anguillid population structures (Minegishi et al 2008;Watanabe et al 2008Watanabe et al , 2011 and silver eel tagging studies (Schabetsberger et al 2015;Jellyman and Tsukamoto 2010) led to ideas about the locations of Indo-Pacific anguillid spawning areas ( Fig.…”
Section: Distribution and Dispersal Of Anguillid Larvaementioning
confidence: 99%
“…Tsukamoto (1990) suggested that A. japonica begins to metamorphose when leptocephali reach 60 mm TL. On the other hand, metamorphosis of leptocephali of A. marmorata and other tropical eel species like Anguilla bicolor pacifica, Anguilla borneensis, and Anguilla celebesensis was found to commence at around 50 mm TL (Kuroki et al 2005(Kuroki et al , 2006, which is considerably smaller than the metamorphosing size of the temperate A. japonica. A. marmorata Cagayan River, the Philippines 19 May 08 1.0 ± 0.18 (13) 1.1 ± 0.14 (13) 1.84 ± 0.46 (13) Hsiukuluan River, Taiwan 20 May 08 0.9 ± 0.10 (13) 1.2 ± 0.18 (13) 2.29 ± 0.72 (13) Kurio River, Japan 6 June 96 0.9 ± 0.14 (15) 1.1 ± 0.17 (15) 2.18 ± 0.61 (15) Overall (μ 2 Cheng and Tzeng (1996).…”
Section: Discussionmentioning
confidence: 99%
“…Castonguay (1987) examined the age and growth of the leptocephali of two Atlantic anguillids in the Sargasso Sea, and there have been studies on the leptocephali of the other species of northern temperate anguillid species, A. japonica Ishikawa et al 2001) and A. australis (Kuroki et al 2008a). There have also been studies on the age and growth of tropical species of anguillid leptocephali in the central Indo-Pacific (Kuroki et al 2005(Kuroki et al , 2006a(Kuroki et al ,b, 2007, and off west Sumatra . Some species for which only a few specimens have been examined for growth rates, such as A. interioris (0.46-0.54 mm/day, Kuroki et al 2006b), and A. obscura and A. megastoma (0.34-0.49 mm/day, Kuroki et al 2008a) are not shown in Table 1.…”
Section: -6 Growth Of Leptocephalimentioning
confidence: 99%
“…One obvious difference is that the maximum size of tropical leptocephali (50-55 mm; Jespersen 1942; Kuroki et al 2009b) is less than that of temperate species (typically about 70 mm) that can reach about 85 mm in A. anguilla, which has the longest larval migration (Tesch 1980;Boëtius and Harding 1985;Kleckner and McCleave 1985;Bast and Strehlow 1990). Kuroki et al (2006a) compared the growth rates of four different tropical anguillid leptocephali (Fig. 31) that recruit to habitats in the central Indonesian Seas.…”
Section: Species By Regionmentioning
confidence: 99%